2021
DOI: 10.31004/basicedu.v5i5.1013
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perception on the Implementation of Home Learning during Covid-19

Abstract: This study aimed to describe the parents’ perception on the benefits and challenges towards home learning during the pandemic. Descriptive qualitative study taking a case in two elementary schools in Kupang, East Nusa Tenggara. There were 20 parents from both schools taken purposively as the sample. 20 questions posted on Google Form as the instrument. The results showed that the implementation of home learning brought two perceptions on the benefits and challenges. The benefits were regarding to possibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…The findings in this study illustrate a distinctive perception of LFH that has not been revealed by other researchers. Research by Lase et al (2022) in rural Gunungsitoli, Ludji & Marpaung (2021) in rural Kupang, and Husain et al (2020) in rural Morotai shows that children and parents do not have experience implementing LFH. However, they have no choice but to adhere to BDR, notwithstanding its restrictions.…”
Section: Preference and Aspirationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings in this study illustrate a distinctive perception of LFH that has not been revealed by other researchers. Research by Lase et al (2022) in rural Gunungsitoli, Ludji & Marpaung (2021) in rural Kupang, and Husain et al (2020) in rural Morotai shows that children and parents do not have experience implementing LFH. However, they have no choice but to adhere to BDR, notwithstanding its restrictions.…”
Section: Preference and Aspirationsmentioning
confidence: 99%
“…This urgency must be considered because, so far, no research has presented the home learning profile of rural children, despite the fact that some of them discuss similar issues; LFH in the countryside. Existing research focuses solely on the impact of LFH (Wahyuningsih, 2021), parents' perceptions (Ludji & Marpaung, 2021), communication barriers and access to digital learning resources (Reddy & Ramesh, 2020;Setiawan & Iasha, 2020), and comparisons of information technology involvement between rural and urban children (Nita et al, 2021). Previous researchers did not address the necessity for information on home learning profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits were concerned the possibility of home learning to provide a personalized experience and flexible system of education, to minimize the possibility of the children to get infected by the Covid-19. Further perception stated that the execution of home learning also brought certain challenges to those parents such as, demanding more expenses to buy the internet quota, causing the children less motivated and irresistible in learning, hovering the work load of the parents, time inadequacy for working parents by spending more time to assist the kids during the learning, increasing the tense between the kids and parents during the learning (7).…”
Section: Dr Aarul Paulmentioning
confidence: 99%
“…Urgensi tersebut perlu diperhatikan karena sejauh ini belum ada riset yang menyajikan profile HL anak-anak pedesaan, walaupun beberapa diantaranya membahas topik serupa; HL di pedesaan. Penelitian yang sudah ada hanya membahas dampak HL (Wahyuningsih, 2021), persepsi orangtua (Ludji & Marpaung, 2021), kendala-kendala komunikasi dan akses terhadap sumber belajar digital (Reddy & Ramesh, 2020;Setiawan & Iasha, 2020), dan perbandingan keterlibatan teknologi informasi antara anak desa dengan anak kota (Nita et al, 2021). Kebutuhan informasi tentang profil HL belum dipenuhi oleh peneliti sebelumnya.…”
Section: Sebagaimana Kajianunclassified
“…Temuan dalam riset ini menggambarkan persepsi khas tentang HL yang belum pernah diungkap peneliti lain. Penelitian Lase et al (2022) di pedesaan Gunungsitoli, penelitian Ludji & Marpaung (2021) di pedesaan Kupang, dan penelitian Husain et al ( 2020) di pedesaan Morotai menunjukkan bahwa anak dan orangtua tidak punya pengalaman melaksanakan HL. Namun mereka juga tidak punya pilihan selain mengikuti HL dengan segala keterbatasannya.…”
Section: Preferensi Dan Aspirasiunclassified